Pengaruh Kepemimpinan, Lingkungan Kerja dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Balikpapan - Yohana Exelsia Sitanggang; Syahril Hasan; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the direct influence of leadership variables, work environment and work discipline on employee job satisfaction at the Balikpapan City Human Resources Development and Personnel Agency (BKPSDM). This study used a sample of 47 respondents with a questionnaire data collection method and analysis tools assisted by SPSS software. The results show that (1) Leadership has a positive and significant effect on Job satisfaction of Employees at the Balikpapan City Human Resources Development and Personnel Agency (BKPSDM); (2) Work Environment has a positive and significant effect on Job satisfaction of Employees at the Balikpapan City Human Resources Development and Personnel Agency (BKPSDM); (3) Work Discipline has no effect on Job satisfaction of Employees at the Balikpapan City Human Resources Development and Personnel Agency (BKPSDM).